45=3x-3(3x+3)

Simple and best practice solution for 45=3x-3(3x+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 45=3x-3(3x+3) equation:



45=3x-3(3x+3)
We move all terms to the left:
45-(3x-3(3x+3))=0
We calculate terms in parentheses: -(3x-3(3x+3)), so:
3x-3(3x+3)
We multiply parentheses
3x-9x-9
We add all the numbers together, and all the variables
-6x-9
Back to the equation:
-(-6x-9)
We get rid of parentheses
6x+9+45=0
We add all the numbers together, and all the variables
6x+54=0
We move all terms containing x to the left, all other terms to the right
6x=-54
x=-54/6
x=-9

See similar equations:

| 45=3x-3(3x=3) | | 35=7y+3-2 | | -7h=-5-8h | | -5x-3(-x+3)=5 | | 2|3y+7|=10y | | -2j=6-j | | -4x+7(2x+4)=-32 | | 3x+5=-99x-10x | | 13y+29=5y-27 | | -18=-4x+2(3x+3) | | -9q=-10q-5 | | 4(3x-3)=5(x+3) | | -18=-4x+2(3x=3) | | (6p+1)(2)= | | -10=-4+4x | | 44=4d | | 6x=2(-2x-4)=-30 | | 14x-(7x-5)=47 | | 7w+28=14w | | 9−2b=-b | | 6p^2=48p=90 | | 1=d-6 | | 9(4x-3)=99x | | -20−5−7n=19−18n | | .40=g/22+0.146 | | 3=3x+2(-x-2) | | 3x+15+11x-5/2=47 | | 10+9j=7j | | 11(x+3)=5(3x+1) | | 4.6b=13.68+7b | | 5y+8-4y=3y-12 | | 17+13s=14s |

Equations solver categories